Chemical Quality and Organoleptic Vegetable Shredded - Ningsih, Reza Rizkia; hartati, fadjar kurnia; Sucahyo, Bambang Sigit (Universitas Dr Soetomo, 2020)
Meat floss is usually made from animal meat. However, recently meatless floss made from vegetables of fruit rinds is gaining popularity. The use of breadfruit is less than optimum, thus processing it to be meatless fruit can increase its value. On the other hand, jackfruit rind has unique characteristics which make it suitable to be processed into meatless floss. This research employed the Completely Randomised Factorial Design treatment. The first factor was two boiling times, namely 8 minutes and 10 minutes. The second factor was the combination ratio of jackfruit rind and breadfruit, namely 25% : 75%; 50% : 50 %; and 75% : 25%. Each treatment was repeated three times. The result indicated that boiling time has a significant influence on the chemical quality of meatless floss, including water and rind content. On the other hand, the ratio of jackfruit rind and breadfruit has significantly affect ash and fat content. Meanwhile, the combination of boiling time and ratio of jackfruit rind and breadfruit significantly affect ash content. The result if Wallis Kruskal test for the organoleptic quality of meatless floss revealed that the boiling time and ratio of jackfruit rind and breadfruit significantly affect colour and crunch, and did not affect flavour and aroma. The L2P2 treatment code, namely 10 minutes boiling time and the ratio 50 %: 50% ratio of jackfruit rind and breadfruit, was the best treatment in this study. This treatment obtained the highest score of 0,68, with water 4,992% content; 6,81% rind content, 5,5 in flavour; 11,563% fat content; 4,9 in colour; 5,1 in aroma; 5,6 in crunch; and 7,937% ash content.